Magnetization and magnetostriction oscillations in a superconducting 2H-NbSe2 single crystal: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Eremenko, V.; Sirenko, V.; Shabakayeva, Yu.; Schleser, R.; Gammel, P. L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The results of a comparative study of the oscillating magnetostriction and absolute magnetization components in the single crystal of the layered superconducting compound 2H-NbSe2 are presented. The measurements were made in the temperature range 1.5-8 K in a magnetic field of 0-20 T with in-plane orientation (normal to the hexagonal axis). The mechanical stress derivative of the extremal cross-sectional area of the Fermi surface is derived from a thermodynamic analysis. The values obtained are considerably higher, by an order of magnitude, than those for other metals, which explains the observed enhancement of the magnetostriction oscillations in comparison with the magnetization oscillations.